Tripartite Motif 8 Contributes to Pathological Cardiac Hypertrophy Through Enhancing Transforming Growth Factor β–Activated Kinase 1–Dependent Signaling Pathways. Issue 2 (February 2017) - Chen, Lijuan; Huang, Jia; Ji, Yan-xiao; Mei, Fanghua; Wang, Pi-xiao; Deng, Ke-qiong; Jiang, Xi; Ma, Genshan; Li, Hongliang
Abstract : Tripartite motif (TRIM) 8 functions as an E3 ubiquitin ligase, interacting with and ubiquitinating diverse substrates, and is implicated in various pathological processes. However, the function of TRIM8 in the heart remains largely uncharacterized. This study aims to explore the role of TRIM8 in the development of pathological cardiac hypertrophy. Mice and isolated neonatal rat cardiomyocytes overexpressing or lacking TRIM8 were examined in several experiments. The effect of aortic banding–induced cardiac hypertrophy was analyzed by echocardiographic, pathological and molecular analyses. Our results indicated that the TRIM8 overexpression in hearts exacerbated the cardiac hypertrophy triggered by aortic banding. In contrast, the development of pathological cardiac hypertrophy was profoundly blocked in TRIM8-deficient hearts. Mechanistically, our study suggests that TRIM8 may elicit cardiodetrimental effects by promoting the activation of transforming growth factor β–activated kinase 1 (TAK1)-p38/JNK signaling pathways. Similar results were observed in cultured neonatal rat cardiomyocytes treated with angiotensin II. The rescue experiments using the TAK1-specific inhibitor 5z-7-ox confirmed the requirement of TAK1 activation in TRIM8-mediated pathological cardiac hypertrophy. Furthermore, TRIM8 contributed to TAK1 activation by binding to and promoting TAK1 ubiquitination. In conclusion, our study demonstrates that TRIM8 plays a deleterious role in pressure overload–induced cardiac hypertrophy by accelerating the activation of TAK1-dependent signaling pathways. Abstract : Supplemental Digital Content is available in the text.